Examination of Catabolic Activities of Enterobacteriaceae Isolated from Soaked Sheep Skins and Cattle Hides - (:unkn) unknown (SOC LEATHER TECHNOL CHEMISTS, 2018)
Detailed examination of the members of family Enterobacteriaceae found on soaked sheepskins and cattle hides offers important information about enteric species on the samples, the efficiency of antibacterial agents used in soaking process against these enteric species and their roles in deterioration of skins or hides during soaking process. Hence, the goal of this study was to examine members of the family Enterobacteriaceae on soaked sheepskins and cattle hides treated with antibacterial agent. In this study, bacterial species belonging to the family Enterobacteriaceae on five soaked sheepskins and ten cattle hides were identified using API (R) 20E test kits and the other biochemical tests. While Citrobacter freundii, Citrobacter koseri, Cronobacter sakazakii, Enterobacter amnigenus, Enterobacter cloacae, Kluyvera intermedia, Morganella morganii, Proteus mirabilis and Providencia rettgeri were isolated from the soaked sheepskins, Citrobacter koseri, Cronobacter sakazakii, Ewingella americana, Kluyvera intermedia, Morganella morganii, Providencia rettgeri, Serratia marcescens, Serratia plymuthica and Serratia rubidae were obtained from the soaked cattle hides. A fairly high percentage of soaked skin and hide samples contained Enterobacteriaceae members which have catabolic activities for deterioration of skins and hides. The presence of the members of Enterobacteriaceae on the soaked skin and hide samples was thought to be related to faecal contamination, the animal itself, environmental sources and inadequate preservation. As a conclusion, efficient antibacterial treatments should be applied in soaking process to kill Enterobacteriaceae members which may adversely affect leather quality.
Keywords: BACTERIAL-POPULATIONS; IDENTIFICATION; SALT